What controls submarine channel development and the morphology of deltas entering deep‐water fjords?. Issue 2 (19th October 2018) - Gales, Jenny A.; Talling, Peter J.; Cartigny, Matthieu J.B.; Hughes Clarke, John; Lintern, Gwyn; Stacey, Cooper; Clare, Michael A.
Abstract: River deltas and associated turbidity current systems produce some of the largest and most rapid sediment accumulations on our planet. These systems bury globally significant volumes of organic carbon and determine the runout distance of potentially hazardous sediment flows and the shape of their deposits. Here we seek to understand the main factors that determine the morphology of turbidity current systems linked to deltas in fjords, and why some locations have well developed submarine channels while others do not. Deltas and associated turbidity current systems are analysed initially in five fjord systems from British Columbia in Canada, and then more widely. This provides the basis for a general classification of delta and turbidity current system types, where rivers enter relatively deep (>200 m) water. Fjord‐delta area is found to be strongly bimodal. Avalanching of coarse‐grained bedload delivered by steep mountainous rivers produces small Gilbert‐type fan deltas, whose steep gradient (11°–25°) approaches the sediment's angle of repose. Bigger fjord‐head deltas are associated with much larger and finer‐grained rivers. These deltas have much lower gradients (1.5°–10°) that decrease offshore in a near exponential fashion. The lengths of turbidity current channels are highly variable, even in settings fed by rivers with similar discharges. This may be due to resetting of channel systems by delta‐top channel avulsions or major offshore landslides, as well as the amount and rate of sediment supplied to the delta front by rivers. © 2018 John Wiley & Sons, Ltd. Abstract :  A model for turbidity channel systems in fjords and deep‐water settings is proposed.  Bimodal delta morphology is linked to river drainage basin character.  Turbidity channel morphology is linked to river discharge, avulsion and mass‐wasting.